Zambia's Jobs Challenge : Realities on the Ground - World Bank (Washington, DC, 2014)
In September 2013, the World Bank launched the second Zambia economic brief, entitled Zambia's jobs challenge: realities on the ground. This report presents response of the youth to the facts and figures shared in the Zambia economic brief. It gives a broad range of discussion, often provocative, as to how Zambia's employment challenges can be tackled. It discusses the issues as diverse as cultural mind-set, absence of entrepreneurial training, weaknesses in labor laws, and low investments in agriculture research and development.